Noninvasive profiling of exercise-induced hypoxemia in competitive cyclists - Siegler, J. C.; Robergs, R. A.; Faria, E. W.; Wyatt, F. B.; McCarthy, J. (Research in Sports Medicine, 2007)
The purpose of this case study was to profile maximal exercise and the incidence of exercise-induced arterial hypoxemia (EIAH) at three different altitudes within a group of competitive cyclists residing and training at 1,500 m. Ten male cyclists (category I or II professional road cyclists: ages, 27.7 ± 6.1; weight, 69.9 ± 6.9 kg) participated in three randomly assigned VO2max tests at sea level (SL), 1,500 m and 3000 m. Arterial saturation (pulse oximetry), ventilation, and power output (PO) were recorded continuously throughout the test. The SaO2 percentages at VO2max were significantly higher at SL when compared with 1500 m (p < 0.001); however, no difference was observed between VO2max values at either altitude (SL: 72.3 ± 2.5 mL·kg-1·min-1, 1,500 m: 70.6 ± 2.3 mL·kg-1·min-1), only when compared with 3,000 m: 63.9 ± 2.1 mL·kg-1·min-1, p < 0.021. Percent SaO2 did correspond with maximal PO, and there was an overall main effect observed between POs as they continually declined from SL to 3,000 m (SL: 403.3 ± 10.6 W; 1,500 m: 376.1 ± 9.8 W; 3,000 m: 353.9 ± 7.8 W; p < 0.0001). The results of this case study revealed that training and residing at 1,500 m did not reduce the incidence of EIAH during maximal exercise at 1,500 m for this selected group of cyclists.